Dilema Hukum Pidana Islam Di Era Modern; Had Al-Sariqah Perspektif Ulama Salaf Dan Ulama Kontemporer - Herfin Fahri (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, In the Islamic Criminal Law system in mass media or books by infidelorientalists and their followers - namely the liberals - they are always cruel andinhumane. The cynical view of the Islamic criminal system was born not because of avanity Islamic criminal system, but there were two main reasons. First, conceptually,the criminal system of Islam is considered contrary to the mindset of the secular orliberal. For example, the death penalty for apostates is considered cruel and wrongnot because of the wrong Islam, but because it is contrary to the principle of religiousfreedom that is held fanatically by the secularists. Second, practically, the criminalsystem that is being applied is indeed not a criminal system of Islam. The law ofcutting hands for thieves is seen as wrong and sadistic not because of the wrongIslam, but because it is contrary to the criminal system of colonial occupation, namelyArticle 362 of the Criminal Code (KUHP). The level of h}ad al-shariqah in Islamiccriminal law (tashri’ al-jina’i) is ¼ dinar or 3 dirhams and 10 dirhams. Regarding theact of cutting hands, Abd al-Qadir 'Awdah confirmed in his book Islamic CriminalLaw or al-Tashri' al-Jina'i al-Islami: Muqaranan bi al-Qanun al- Wad'i that in had alshariqah not all thieves must cut off their hands. There are certain levels andindividual guidelines that govern them. Keyword: Islamic Criminal Law, Had al-Sariqah